Evolution of starved coastal systems in relation to seal level rise and ocean acidification (Mediterranean sea) - Simone Simeone; Emanuela Molinaroli; Alessandro Conforti; Walter Brambilla; GIovanni De Falco (Elsevier, 2018)
The adaptation of coastal barriers to climate change depends on the rate of sea level rise (SLR), the availability of sediments, the accommodation space for sediment deposition following the sea transgression and the geological inheritances. We investigated the morphological evolution of a Mediterranean starved coastal system (western Sardinia island) during the last 5 ky to infer the adaptation of such systems in relation to the SLR scenarios. This coastal system is characterised by the absence of land -derived terrigenuos sediment input, and by the presence of relict siliciclastic and biogenic sediments of marine origin. Grainsize, petrography and mineralogy data coupled with multibeam and lidar data and radiocarbon dating were used to deduce the evolution of such system during the last 5ky. In the northern side the relict siliclicatic sediments are predominant (about 80%). This area is characterized by well cemented drowned barriers from 16m to 9 m of depth. The present barriers are beach ridges and accounts low amount of sediments. In the southern side a large amount of biogenic carbonate sediment (about 50% of the total mass) contribute to build a more complex beach and dune systems with the formation of a coastal wedge and cliff top and parabolic dunes in the landside area. The amount of biogenic carbonate sediments input from the sea to the land is the main factor that controls the evolution of this coastal system in relation to climate changes. Where this amount is low the main forcing of global change will be the SLR, which can lead to a barriers roll over in relation to the accomodation space. Where the biogenic carbonate amount is high the coastal systems will be affected simultaneously by SLR and Ocean Acidification which can lead to shoreline retreat and dune erosion and a decreasing on carbonate sediment budget.